(untitled) (Revista ESASP - Revista Científica Virtual da Escola Superior de Advocacia da OAB/SP, 2025)
It reveals the substantial environmental costs of artificial intelligence, demystifying its apparent immateriality and demonstrating the need to rethink technological development through the lens of sustainability. (Received: September 2025 | Accepted: November 2025)